Vaccine research and development capacity in Central and West Asia: A path toward sustainable vaccine R&D programs - Hare, Jonathan; Riggall, Giovanna; Bongers, Alexander; Ramesh, Kirthi; Kokareva, Larissa; Chin, Brian (Frontiers in Public Health, 2023)
The ability to support a comprehensive vaccine research and development (R&D) portfolio from a health security perspective has taken on enhanced significance over the past three years whereby countries that had existing vaccine R&D infrastructure (G7, Russia and China) have been at the forefront of global efforts to combat COVID-19. Few countries outside of these key players have the infrastructure necessary to develop national vaccine programs, though this is beginning to change with investment across many low- and middle-income countries. These same opportunities exist for countries in Central and West Asia, and in this perspective, we highlight the existing infrastructure and expertise across seven countries (Armenia, Azerbaijan, Georgia, Kazakhstan, Kyrgyzstan, Tajikistan, and Uzbekistan) and propose opportunities for enhanced collaboration along with a bold proposal for establishing a new-build, regional vaccine translational research institute to facilitate the development of a robust, regional vaccine R&D environment to combat existing and future health challenges.